Success Frequency of Radiofrequency Catheter Ablation in Narrow Complex Tachycardia - Muhammad Rehan Khan (Gomal Journal of Medical Sciences, 2013)
Background: Narrow-complex tachycardia is a common arrhythmia. The objective of this study was to determine the success frequency of radiofrequency ablation in patients with narrow complex tachycardia. Material and Methods: This cross sectional study conducted in Department of Cardiology, Lady Reading Hospital Peshawar, from January 2008 to January 2009. All patients with narrow complex tachycardia were included. Radiofrequency catheter ablation procedure was carried. The procedure was considered successful when post ablation tachycardia could not be induced within two minutes of isoprenaline 2µg/ minute with infusion pump. The demographic variables were gender, age in years, age grouping and the research variables were type of narrow complex tachycardia, success and complications of procedure. The data was analyzed for fequeccy (number) and relative frequency (%). Results: Out of 50 patients 24 (48%) were male and 26 (52%) wer female. The mean age of patients was 39.72 ±13.31(13-70) years. Ten (20%) patients were in age group of upto 25 years, 31 (62%) were in age group of 26-50 years and nine (18%) were in age group of more than 50 years. The frequency of successful procedure was 49 (98%) all over. Out of 50 patients with narrow complex tachycardia, 28 (56%) patients were of atrioventricular nodal reentry type, 17 (34%) patients were of atrioventricular reentrant tachycardia type, 4 (8%) patients were of atrial tachycardia and only one (2%) patient was of atrial fibrillation type. Conclusion: Radiofrequency catheter ablation in narrow complex tachycardia is a reasonable therapeutic approach.